KEMATANGAN EMOSI ANAK JALANAN DI LAMPU MERAH DEPAN KANTOR GUBERNUR KOTA PEKANBARU RIAU - Wahyuni, Sisri; Rosmawati, Rosmawati; Yakub, Elni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the emotional maturity of street children. The study population was street children who were in the red light area in front of the Pekanbaru Riau governor's office. Emotional maturity is related to a person's ability to act ethically and to demonstrate the ability to control oneself. This type of research uses descriptive research. The subjects of this study were 3 people who were taken using accidental (insindental) techniques. The instruments in this study are in the form of observation and interviews. Children who experience emotional maturity are able to develop and accept love, emotional control, tolerance for frustration and the ability to cope with tension. The results showed that street children at the red light in front of the governor's office in Pekanbaru, who had emotional maturity, were able to develop empathy for their fellow colleagues and help each other in times of need, had high respect for older people and respect for each other. his friends while working on the streets, those who work on the streets are his own will without coercion from others he works on the streets to help the economy of his family.Key Words: emotional maturity, street children